Where Does the Development of Psychology Lead? - Petrosyan, Gagik (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
The problem of development of psychological knowledge is one of the central methodological problems of psychology. In the paper, the author shows that psychology cannot develop by means of the development of empirical sciences. In psychology, anomalies are not possible, i.e. such facts under the influence of which psychological theories and concepts would change. New psychological theories emerge not by increasing the factual volume, but by changing the theoretical content of science. All theories in psychology proceed from the same factual data. Only the explanations given to this data in different psychological theories and concepts do differ. Therefore, the only way to develop psychology, according to the author, is theoretical development - integration, and generalization of psychological knowledge.